(3SMH GdbQGQGJ GdEOGQjI ai GdbGfhf GdchjJi (B: s (3OQGSI ebGQfI (B/ s - (3agO jhSa YHOGddg GdLeYIs; (3QCaJ EHQGgje ahOI s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2016)
(3Ef SMH GdbQGQ EOGQjkG gh ELQGA JfaQO Hg GdSdWI GdEOGQjI jNhdgG GdQLhY Yf bQGQGJ SHb UOhQgG YfgG h jfJL Yfg JLQjO GdbQGQ ef bhJg GdbGfhfjI h eMh CKQg HGdfSHI ddeGVi h GdeSJbHd(B: (3h cCf de jcf dg hLhO(B. (3h dbO GSJbQ GdbVGA GdEOGQi Ydi Cf GdbQGQGJ GdJi JhdO MbkG Ch eQcRkG TNUjkG ddCaQGO dG jLhR SMHgG ai Ci hbJ eJi UOQJ SdjeI h Pdc GSJLGHI dOhGYi GdeUdMI GdYGeI GdJi JbJVi GSJbQGQ Jdc GdbQGQGJ(B. (3CeG HGdfSHI ddbQGQGJ GdaQOjI ZjQ GdeTQhYI aGdbGYOI YcS Pdc EP jLH Ydi LgI GdEOGQI Cf JSMHgG GdJRGekG efgG HMce GdbGfhf h JUMjMkG ddChVGY GdeNGdaI dg(B. (3jgOa GdHMK Edi GdJYQja HeSCdI SMH GdbQGQGJ GdEOGQjI(B: (3h eOi GdSdWI GdJbOjQjI GdeefhMI ddEOGQI h GdeDKQGJ GdJj JDKQ YdjgG HUOO gPg GdeSCdI(B. (3GdJejjR Hjf SMH GdbQGQGJ GdEOGQjI hChLg EfgGA GdbQGQ GdEOGQj GdCNQi hCgegG EdZGA GdbQGQ GdEOGQj(B. (3HMK eOi JCKQ SdWI GdEOGQI ai SMH GdbQGQ GdEOGQi HGdeHGOF GdJi SGQ YdjgG GdbVGA GdEOGQi(B: (3h ef CHQRgG eHOC GdeTQhYjI(B: (3h eHOC YOe QLYjI GdbQGQ GdEOGQi(B. (3HMK eOi JCKjQ SMH GdbQGQ GdEOGQi ai GdMbhb GdJi GcJSHgG GdCaQGO ef GdbQGQ GdeSMhH(B: (3h ai GSJbQGQ GdMbhb h GdeQGcR GdbGfhfjIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdYGes
(3HHdjhLQGajG(B: (3UaMGJ (B487-498s
Keywords: (3GdbQGQ GdEOGQjs; (3GdbGfhf GdchjJis; (3GdbQGQGJ GdEOGQjIs; (3SMH GdbQGQGJ GdEOGQjIs; (3GLQGAGJ SMH GdbQGQ GdEOGQjs; (3GdeSFhdjI GdGOGQjIs; (3GdbGfhf GdEOGQjs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes